Branding Image melalui Penerapan Pendidikan Inklusif dalam Meningkatkan Daya Saing Madrasah - Moh. Fachri; Fathor Rozi; Tamimullah Tamimullah (LP2M STIT Palapa Nusantara, 2022)
This study aims to analyze and understand the brand image applied through inclusive education to improve the competitiveness of madrasas. Brand image assistance is carried out to improve the quality of institutions and institutions from a negative image. This research was conducted through a case study-type approach. This research was conducted at the MI Nurul Yaqin Kertosono Gading Probolinggo institution. Results Based on the study shows that; First, the institution has implemented a brand image through the implementation of inclusive education in increasing the competitiveness of madrasas. Second, the performance of an inclusive branding image is carried out in several stages, including; Branding Analysis, Establishing Partnerships, Implementation of Inclusive Education, and Evaluation. The implications obtained from institutions with brand image through the implementation of inclusive education are; The institution has a new idea in the quality and quality assurance of the institution, the revolutionary madrasa is dignified and embraces all circles so that it is of high quality and ready to compete.